2013
DOI: 10.1016/j.compstruct.2012.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Loading and fracture response of CFRP-to-steel adhesively bonded joints with thick adherents – Part II: Numerical simulation

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In-depth and extensive studies have been conducted on the factors influencing the properties of adhesively bonded structures of composite materials, such as thickness of the adhesive layer [8], gaps in the adhesive layers [9], temperature [10][11][12], and loading forms [13,14], and even reports on nanoscales have been produced [15,16]. The methods used have included experimental tests [17][18][19], finite element simulations [20,21], and analytical methods [22]. However, most objects employed in the research have been limited to the connection structures of resin-based fiber reinforced composite materials at temperatures below 400 • C [12].…”
mentioning
confidence: 99%
“…In-depth and extensive studies have been conducted on the factors influencing the properties of adhesively bonded structures of composite materials, such as thickness of the adhesive layer [8], gaps in the adhesive layers [9], temperature [10][11][12], and loading forms [13,14], and even reports on nanoscales have been produced [15,16]. The methods used have included experimental tests [17][18][19], finite element simulations [20,21], and analytical methods [22]. However, most objects employed in the research have been limited to the connection structures of resin-based fiber reinforced composite materials at temperatures below 400 • C [12].…”
mentioning
confidence: 99%
“…The number of degrees of freedom is reduced appreciably by this approach because the adherends and the adhesive use the same node. Anyfantis and Tsouvalis's work [13] was focused on the numerical simulation of single-lap bonded joints, based on cohesive zone modelling techniques. The models were built in a 3D FE space.…”
Section: Introductionmentioning
confidence: 99%
“…Two CFRP sheets were adhesively bonded by Casas-Rodriguez et al [6] and the impact-fatigue performance investigated. Anyfantis and Tsouvalis [7] fabricated joints of CFRP and mild steels by adhesive bonding. They found that an increase (200 %) of overlap length resulted in an increase (100 %) to the joints' lap shear strength.…”
Section: Introductionmentioning
confidence: 99%